University Copyright Between Infringement and International Protection "A Model Study" - Kessi, Karima; Daas, Kamel (Journal of Legal Studies and Researches, 2023)
The infringement of copyright university is one of the most dangerous types of infringement, and it is the aim that leads to addressing this issue in order to reach one conclusion which is that infringement in all its forms is a crime punishable by law and he gives to author the right of protection whether it is international or national. Therefore, infringement and protection are two sides of the same coin.